Physical activity, physical frailty and depressive symptoms among Chinese male and female older adults: do different indicators make a difference? - Wang, Ying; Wang, Xue; Zhu, Xinyu; Sun, Yawen; Han, Buxin; Chen, Tianyong (Frontiers in Public Health, 2023)
Objectives Older adults become more inactive and frailer with aging. Physical status is closely linked to mental health, but it is unclear which physical indicator is more strongly associated with depressive symptoms in older adults. The present study aimed to compare relationships between self-reported physical activity, physical frailty (muscle mass, muscle strength, and gait ability) and depressive symptoms in community male and female older adults. Methods A total of 1,180 adults aged 60 years and older were recruited to participate in this study from a Chinese community receiving annual check-up service from September 2018 to May 2019. Physical activity was assessed by the International Physical Activity Questionnaire (IPAQ). The Bio-electrical Impedance Analyzer was used to determine the muscle mass. As the indicators of muscle function, grip strength and gait ability were assessed by the dynamometer and Timed Up and Go Test (TUGT), respectively. The 15-item version of Geriatric Depression Scale (GDS-15) was used to examine depressive symptoms. Demographic variables, health status and sleep quality were collected using questionnaire. Results 11.8% men and 11.9% women reported depressive symptoms. Logistic regression showed that depressive symptoms was associated with low grip strength (OR = 2.42, 95% CI: 1.04–5.63), slow gait ability (OR = 3.60, 95% CI: 1.28–10.13) in older males, and associated with low level of self-reported physical activity (OR = 3.85, 95% CI: 2.00–7.42) in older females. No significant association was found between muscle mass and depressive symptoms. Conclusion There were gender differences in the relationship between physical activity, physical frailty, and depressive symptoms. Grip strength and gait ability may be a better indicator of frailty for predicting depressive symptoms in older men while physical activity may be useful in predicting depressive symptoms in older women.